Assessment and Characterisation of Ireland’s Green Tides (Ulva Species) - Wan, Alex H.L.; Wilkes, Robert J.; Heesch, Svenja; Bermejo-Lacida, Ricardo; Johnson, Mark P.; Morrison, Liam (PLoS, 2017)
Enrichment of nutrients and metals in seawater associated with anthropogenic activities can threaten aquatic ecosystems. Consequently, nutrient and metal concentrations are parameters used to define water quality. The European Union's Water Framework Directive (WFD) goes further than a contaminant-based approach and utilises indices to assess the Ecological Status (ES) of transitional water bodies (e.g. estuaries and lagoons). One assessment is based upon the abundance of opportunistic Ulva species, as an indication of eutrophication. The objective of this study was to characterise Ireland's Ulva blooms through the use of WFD assessment, metal concentrations and taxonomic identity. Furthermore, the study assessed whether the ecological assessment is related to the metal composition in the Ulva. WFD algal bloom assessment revealed that the largest surveyed blooms had an estimated biomass of 2164 metric tonnes (w/w). DNA sequences identified biomass from all locations as Ulva rigida, with the exception of New Quay, which was Ulva rotundata. Some blooms contained significant amounts of As, Cu, Cr, Pb and Sn. The results showed that all metal concentrations had a negative relationship (except Se) with the Ecological Quality Ratio (EQR). However, only in the case of Mn were these differences significant (p = 0.038). Overall, the metal composition and concentrations found in Ulva were site dependent, and not clearly related to the ES. Nevertheless, sites with a moderate or poor ES had a higher variability in the metals levels than in estuaries with a high ES.
Keywords: Algas marinas - Crecimiento; Efectos de la calidad del agua; Ulva; Green tides; Ireland; Metal content